Characteristics, preferences and motivation of avid non-fiction readers. (3rd April 2018) - Merga, Margaret Kristin; Mat Roni, Saiyidi
Abstract : Purpose: This paper aims to provide insights into the characteristics of avid non-fiction book readers, exploring their typical demographic characteristics in relation to reading volume and frequency. It also investigates their comparative library usage in relation to avid fiction readers, as well as their motivation to read, and barriers to reading. Findings from the subset of self-identified avid non-fiction readers from the 2015 International Study of Avid Book Readers are interrogated to provide insights into this under-researched group. Design/methodology/approach: The authors have used a single-stage mixed-methods approach, using data from both qualitative and quantitative items in an international survey. Findings: The quantitative data analysis of this study suggests that avid non-fiction book readers were more likely to be men and older than avid fiction readers, and that they also tended to read less frequently, though avid non-fiction readers tended to read a greater volume of books. Avid fiction readers reported greater library usage, and thus unsurprisingly were found to have a greater borrowing tendency than non-fiction readers. Our qualitative findings around reading motivation identified a range of recurrent themes. The authors also found three key barriers to reading: time, book access and concentration. Originality/value: The findings of this study provide unique insights into the characteristics, preferences and motivation of avid non-fiction readers, with the relationship between pleasure and the reading of non-fiction of particular interest.